MENELAAH KEMISKINAN DI INDONESIA PERSPEKTIF EKONOMI POLITIK - Oktavianti, Henny (Journal of Indonesian Applied Economics, 2008)
The poverty alleviation has been a main problem in Indonesia for a long time. Thenumbers of poverty has been increased for more than onethird in the crisis that hasreturned into the beforecrisis period. Meanwhile, Indonesia has experienced a greattransformation in social and political in line with the development of full spirit ofdemocracy  by  the  existence  of  government’s  decentralization,  and  also  a widertransparency than what we have in the past. The commitment of the government inalleviating poverty has been  stated  in Rencana Pembangunan Jangka Menengah(RPJM)  20052009  which  based  on  the  Strategi Nasional  PenanggulanganKemiskinan  (SNPK). However,  the  rate  of  poverty  is  still  high,  viewed  from  anyfactors. This paper focuses on the discussion of poverty that did not abate in spite ofvarious poverty alleviation programs has been announced by the government. Thewriter has analyzed the absolute phenomena of poverty based on the political view,which  the variables are related  to  the economic growth since  the basic  economicactivities could affect the level of poverty (Weede, 1986, saunders, 1986, Castles,1990, 1991, in Lane & Ersson, 2002).Keywords: poverty, Indonesia, economic and political perspectives